2015
DOI: 10.3329/nimcj.v6i1.23150
|View full text |Cite
|
Sign up to set email alerts
|

Fungal sepsis and Indications of antifungal prophylaxis and treatment in neonatal intensive care units : A review

Abstract: not availableNorthern International Medical College Journal Vol.6(1) 2014: 6-8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…This study showed that male sex was a significant predictor of the development of FI in ELBW infants. Previous studies reported that male sex was identified as a risk factor for FI, even though Candida is considered as a commensal organism in the female genitourinary tract . Thus, sex in FI is considered to be a stronger risk factor for infection than fungal colonization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that male sex was a significant predictor of the development of FI in ELBW infants. Previous studies reported that male sex was identified as a risk factor for FI, even though Candida is considered as a commensal organism in the female genitourinary tract . Thus, sex in FI is considered to be a stronger risk factor for infection than fungal colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension with inotropic treatment within 7 days of birth was also a risk factor associated with mortality in FI. Although hypotension may be due to poor patient status, considering that circulatory shock may be one of the risk factors of FIs, hypotension is an important risk factor for the development of FIs in ELBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques can be used to reduce infectious particle load to minimal levels or at levels where conventional medication and the body’s own immune system can fight the infection. Thus, they may be particularly useful for individuals experiencing immunosuppression or young children for whom antibiotics and antifungal medication can be highly toxic [44, 45]. Extending these concepts further, future work will include tubes coated with pathogen-killing agents.…”
Section: Discussionmentioning
confidence: 99%
“…The current therapeutic options that are available to treat fungemia among newborns and children are based on clinical trials in adults, since there are few comparative studies of antifungal agents in infants. The optimal treatment of fungal infection in this special population requires detailed studies on pharmacokinetics, safety and efficacy of antifungal therapies [51][52][53][54].…”
Section: Treatment Of Neonatal Fungal Infectionsmentioning
confidence: 99%
“…Fluconazole prophylaxis is effective in reducing the rate of colonization and progression to systemic infection in nursery; on the other hand, some studies have revealed that prophylactic or empiric therapy with antifungal agents may be associated with changes in Candida ecology and antifungal agent susceptibility. Actually, the fluconazole dose recommended for neonates is 6 mg/kg/ day, and maintenance doses currently used in NICUs in Europe is often higher, between 6 and 12 mg/kg [53,[56][57][58].…”
Section: Treatment Of Neonatal Fungal Infectionsmentioning
confidence: 99%